Development of Dasa Darma Values at MAN Purwakarta - Gustiana; Muhammad Ridwan Effendi; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the diversity of Scout members in instilling Dasa Darma values. Data collection techniques in this study were through observation, interviews and documentation of several students who were active in the MAN Purwakarta Scout Movement extracurricular activities. Based on the research analysis, it was concluded that the Scout members of MAN Purwakarta believe in the pillars of faith and carry out the creed, pray, give alms, fast and behave in love for nature, love fellow human beings, have a patriotic spirit, have good manners, have a knight spirit, obey, carry out deliberations, help each other, steadfast in facing trials, diligent, skilled, frugal, careful, modest, always self-disciplined, courageous in truth, loyal to nation and religion, carrying out duties and orders properly, not lying, thinking that is directed towards goodness, not saying dirty words and rude, does not do things that harm either themselves or others in accordance with the values reflected in the Dasa Darma of the Scout Movement